THE POSITION OF MINANG-CHINESE RELATIONSHIP IN THE HISTORY OF INTER-ETHNIC GROUPS RELATIONS IN PADANG, WEST SUMATRA - Laila Kholid Alfirdaus; Eric Hiariej; Farsijana Adeney-Risakotta (Humaniora, 2016)
Generally studies on pribumi and Chinese relationship in Indonesia are dominated with conflict perspectives. In fact, in practice, the relationship between the two groups can be very dynamic. Amongst social tension arose between them, there are often stories about social harmony, social engagement and social cohesion. This is also what we found in the Minang-Chinese relationship in Padang, West Sumatra. The Minang-Chinese relationship in Padang, West Sumatra, in current period has been not only about social tension. In spite of the strong tension arose due to differences in ethnicity and religious belief, they are strongly tied in running local trading, political party, and other areas of public policy making. Competition in economy often stands together with cooperation. This similarly works in local politics, and, recently, community recovery post 2009-earthquake. Such dynamic relationships is inseparable from ethnic politics constructed throughout Padang history in the past. This paper sees that the relationships of Minang and Chinese are inseparable from the ethnic politics constructed throughout Padang history. This paper tries to portray briefly the journey of Minang and Chinese relationship in Padang and the politics that contextualizes the making of that relationship based on literature research and in-depth interviews. Despite its shortness, this paper is supposed to provide background information for those interested in discussing the issue of ethnicity in Padang and West Sumatra.